Pusat Kesenian Di Desa Bungaya, Karangasem dengan Pendekatan Eco-Cultural - Ida Bagus Yoga Artha Wiguna Wiguna; Ni Putu Ratih Pradnyaswari Anasta Putri; I Wayan Widanan (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2022)
Bungaya Village, is one of the cultural tourism villages because the village has its own uniqueness, and has seven tourism potentials, one of which is historical heritage, unique traditional activities and nature. However, as time goes by, most of the Bungaya Village Area is now untouched by development, which is one of the reasons for the lack of special attractions for tourists, such as dances, weaving and other cultural activities which tend to be rarely carried out. only performed at ceremonies in certain months and not supported by commercial facilities. From this, it results in a decrease in function as a cultural tourism village area which will have an impact on decreasing the number of tourists and causing a loss of existence compared to other cultural tourism villages such as Tenganan village. Therefore, the need to build an object that can maintain and improve this area by establishing an Art Center with an Eco-Cultural Approach arises from the natural potential of the Bungaya Village and the diversity of arts and culture which is a local identity and has been inherited from generation to generation. hereditary. By using the architectural theme of contextualism, you can present buildings that are able to pay attention to the surrounding conditions so that their existence can be harmonious and unified, so that the potential in the environment is not neglected.